The Case for an Elderly Targeted Stroke Management - Fustinoni, Osvaldo (Frontiers in Neurology, 2011)
The elderly, in whom atrial fibrillation is most prevalent, carry the greatest risk, undergoing more recurrent, deadlier strokes, with bigger deficits, slower recoveries, and more comorbidities. Age-related cerebral changes might undermine the benefit of established stroke treatments. Nevertheless, the elderly should probably also undergo thrombolysis for ischemic stroke: they do not bleed more, and die not because of hemorrhage but of concomitant illnesses. Beyond natural bleeding risks, atrial fibrillation in advanced age has a high embolic potential if not anticoagulated. Standard or lower intensity warfarin anticoagulation prevents embolic stroke in the elderly with a hemorrhage risk even lower than aspirin. Excess anticoagulation hazards are prevented with lower starting doses, stricter corrections, more frequent INR monitoring. Direct thrombin inhibitors have recently shown a benefit similar to warfarin with fewer hemorrhages. Antihypertensives probably help 80-plus stroke patients as well, but the risk/benefit of lowering blood pressure in secondary stroke prevention at that age is uncertain. In summary, emerging data suggest that stroke management should be specifically targeted to the elderly.